Context-Aware Crowd Monitoring with Dynamic Multi-User Tracking Data - Mustakim hanifa, A.; Ameen zulkifli, M.; omar, nasiroh; m. Zamani, azmina; masrom, suraya (International Journal of Engineering and Technology, 2018)
Â Monitoring small crowd of people as tourists in different country always create recurrence issues to their tour-guides such as someone is lost somewhere, losing important documents and getting sick in the middle of the crowd. Similarly, during the Hajj season, such issues occur while millions of Muslims are gathered in two popular cities, Mecca and Medina, of Saudi Arabia. At the peak of the Hajj season, Mecca is identified as the most crowded place when pilgrims all over the world along with their respective tour-guides known as Mutawwif are resided in the city. Thus, communication between the crowd and their respective tour guides offers useful dynamic multi-user tracking data which is essential for close monitoring purposes. This study explores the usage feasibility of dynamic multi-user tracking data in order to provide a context-aware and simple communication means in the form of mobile application to both pilgrims and Mutawwifs for resolving their recurrence issues. The application can be used by the pilgrims to send current location and purpose for contacting the Mutawwif. At the same time, the Mutawwif is able to locate their respective pilgrims and aware of their pilgrimsâ€™ current location and needs. The prototype of the system is developed by using software engineering approach to test the feasibility of using multi-user tracking data in such situation. The prototype has been evaluated and fulfilled the intended requirements for monitoring small crowd. As a conclusion, the prototype offers an alternative for Malaysian Mutawwifs to aware of pilgrimsâ€™ issues and track their need and location at real time during Hajj season. Similarly, the pilgrims also can communicate their needs and problems to their respective Mutawwifs.Â Â